Electronic participation : 12th IFIP WG 8.5 international conference, ePart 2020, Linköping, Sweden, August 31-September 2, 2020, Proceedings /: 12th IFIP WG 8.5 international conference, ePart 2020, Linköping, Sweden, August 31-September 2, 2020, Proceedings. (2020) - Unknown
No abstract available